2001
DOI: 10.1577/1548-8454(2001)063<0049:tontnt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Nitrite to Nile Tilapia: Effect of Fish Size and Environmental Chloride

Abstract: Small (4.4 ± 1.50 g; mean ± SD) Nile tilapias Oreochromis niloticus were more tolerant of nitrite than large (90.7 ± 16.43 g) fish. The 96‐h median lethal concentration of nitrite‐N to small fish was 81 mg/L (95% confidence interval = 35–127 mg/L) compared with 8 mg/L (4–11 mg/L) for large fish. Addition of chloride to test water (as either calcium chloride or sodium chloride) protected both small and large fish from nitrite. Sodium chloride and calcium chloride appeared to be similarly effective in inhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 9 publications
0
36
4
Order By: Relevance
“…While nitritenitrogen is not as toxic as unionised ammonia, it is harmful to aquatic organisms and must be removed from the system. The reported findings are much lower than the 96-h median lethal concentration of 81 and 8 mg/l recommended for small and large O. niloticus, respectively (Atwood et al 2001). The present levels are also within the recommended limits of less than 0.3 and 0.2-10 mg/l for nitrite-nitrogen and nitrate-nitrogen, respectively, for aquaculture pond waters (Boyd and Tucker 1998).…”
Section: Discussioncontrasting
confidence: 57%
“…While nitritenitrogen is not as toxic as unionised ammonia, it is harmful to aquatic organisms and must be removed from the system. The reported findings are much lower than the 96-h median lethal concentration of 81 and 8 mg/l recommended for small and large O. niloticus, respectively (Atwood et al 2001). The present levels are also within the recommended limits of less than 0.3 and 0.2-10 mg/l for nitrite-nitrogen and nitrate-nitrogen, respectively, for aquaculture pond waters (Boyd and Tucker 1998).…”
Section: Discussioncontrasting
confidence: 57%
“…When one takes into consideration that nitrite is a blood poison, it seems logical that fry could survive for a longer time when the oxygen-carrying capacity of blood is reduced than would an adult who depends on oxygen delivered by the blood stream for survival (Bartlett and Neumann, 1998). In a lethal experiment conducted on Nile tilapia (Oreochromis niloticus) Atwood et al (2001) found out that tolerance to nitrite was significantly affected by the fish size (the difference in age and sexual development between both groups was not mentioned). The 96hLC 50 for smaller fish (average weight 4.4 ± 1.50 g) was 81 mg/l N-NO 2 -and larger fish (90.7 ± 16.43 g) demonstrated a 96hLC 50 of 8 mg/l N-NO 2 -.…”
Section: Fish Size and Agementioning
confidence: 99%
“…Addition of chloride ions (Cl − ) to culture water seems reduce the nitrite toxicity in most freshwater fish (Lewis & Morris 1986;Atwood et al 2001), increasing the nitrite tolerance more than 30-fold (Wisse & Tomasso 1989). According to Doblander and Lackner (1997) part of the nitrite taken up will be detoxified by erythrocytes in fish.…”
Section: Higher Organismsmentioning
confidence: 99%